Exploring Islamic tourism in Malaysia - Ab Rahman, Suhaimi; Laderlah, Siti Anis (AESS Publications, 2018)
Malaysia aims to be the global halal hub by 2020. Halal does not only cover products but also services. Tourism is part of services and becoming one of the major income for the country. In order to sustain the receipt of Muslim tourists, the government has announced Islamic tourism as one of tourism products in Malaysia. As such, there is no clear guideline on the concept of Islamic tourism to be offered to prospective tourists. This paper is an attempt to develop the concept of Islamic tourism and the practice as experienced by Malaysia will be indicators for future development of the concept of Islamic tourism. The data gathered and analyzed primarily based on qualitative method. Both observation and content analysis have been used to understand the acceptable practice of Islamic tourism. We propose that Islamic tourism is established upon economic, cultural, religious, social, spiritual and physical dimensions. It is also found that the government was very serious to develop Islamic tourism as one of tourism products and the establishment of Islamic Tourism Centre in 2008 was the proof. The initiative taken by the government was successful when a total of Arabs came to Malaysia in 2009 was 284,890 and increase year by year.